EFL Teachers' Perspectives on the Role of English in Two Mexican Private Universities - Colette Despagne (Universidad Nacional de Colombia, 2019)
In Mexican higher education, the spread of English has become a tool in the internationalization process of universities. However, language has been sidelined in the discourses of globalization and internationalization. Hence, this ethnographic case study aims to look at the spread of English in Mexican higher education through two private universities. It focuses on the universities' internationalization process, and how English as a foreign language teachers perceive the role of English in this process. Findings show that while English as a foreign language teachers support linguistic ideologies that promote the spread of English as a natural and apolitical phenomenon, at the same time they also warn of ideological implications such as language hierarchies, cultural homogenization, and English linguistic discrimination.